2021
DOI: 10.1111/jdv.17776
|View full text |Cite
|
Sign up to set email alerts
|

‘Retraction artefacts’ in basal cell carcinomas do not result from fixation but likely arise by degradation of extracellular matrix during tumour growth

Abstract: served as a member of expert panels on cutaneous adverse reactions for Pfizer INC and received financial support for congress participation from Bristol-Myers Squibb, Novartis Pharma and Amgen GmbH. Maja Mockenhaupt currently serves as a member of expert panels on cutaneous adverse reactions for Boehringer International GmbH and Paul-Ehrlich-Institut (PEI). Johannes Kohlmann and Robin Reschke have no conflict of interests to declare. AcknowledgementThe patients in this manuscript have given written informed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…On the other hand, other researchers disagree [ 64 ]. Newer studies, such as the one by Mentzel et al, showed that the extracellular matrix breakdown that happens during tumor growth is the source of such clefts [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, other researchers disagree [ 64 ]. Newer studies, such as the one by Mentzel et al, showed that the extracellular matrix breakdown that happens during tumor growth is the source of such clefts [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings were corroborated by Ulrich et al’s research, which went even further to state that in the peritumoral clefts, there are mucin deposits [ 60 ]. Another study concluded that the origin of these spaces comes from the extracellular matrix degradation that occurs during tumor growth [ 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a persistent question remains: why does this distinctive characteristic prominently manifest in basal cell carcinoma (BCC) tumors and rarely in other scenarios?" Various theories have been proposed regarding the formation of spaces around BCC tumors, including changes in desmosomal structures leading to detachment of the basal membrane [1] or disruption by enzymes [2], or even laminar detachment of peripheral tumoral cells [1]. However, while these theories offer potential explanations, they have not been conclusive.…”
Section: Editorialmentioning
confidence: 99%
“…The appearance of these peritumoral clefts or palisading features surrounding the characteristic basaloid tumor cells has intrigued researchers and pathologists for years. While the simplest explanation may be attributed to tissue retraction or artifacts [ 1 , 2 ], it persists even under in vivo imaging [ 2 ]. Additionally, a persistent question remains: why does this distinctive characteristic prominently manifest in basal cell carcinoma (BCC) tumors and rarely in other scenarios?"…”
Section: Editorialmentioning
confidence: 99%
“…[3] Retraction artifact was attributed to mucin shrinkage occurring during fixation and staining of the specimen; however, in a recent paper, Mentzel et al suggested the possibility of extracellular matrix degradation (that occurs during tumor growth), leading to the formation of retraction artifact. [9] The tumor shows centrally located nuclei, which are crowded with scattered, mitotic figures, and necrotic bodies. The presence of a mucinous stroma distinguishes BCC from other basaloid tumors arising from the skin.…”
Section: Introductionmentioning
confidence: 99%